Keniscayaan Inklusivisme dan Kedewasaan Beragama Untuk Indonesia Damai - Ricky Ronaldo; Dwi Wahyuni (JIA (Jurnal Ilmu Agama), 2022)
This study aims to explore the understanding of inclusivism in religions to create religious maturity so that all kinds of society disintegration can be avoided. This study was conducted using library data collected, understood, and analyzed. Through collecting, analyzing and understanding lists of literature references it can be concluded that if every human being can be religiously mature and wise, surely there will be no more conflict in the name of religion and humanity will grow into a better civilization. Therefore, in order to create a harmonious Indonesia, it is important to maintain the spirit of inclusiveness and maturity in religion as a necessity in order to maintain the unity of the Unitary State of the Republic of Indonesia.